2013
DOI: 10.1212/01.wnl.0000437313.80913.2c
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia involvement in amyotrophic lateral sclerosis

Abstract: ALS is associated with widespread basal ganglia involvement. Caudate nucleus, hippocampus, and nucleus accumbens atrophy are key features of ALS. Dysfunction of frontostriatal networks is likely to contribute to the unique neuropsychological profile of ALS, dominated by executive dysfunction, apathy, and deficits in social cognition. Our quantitative imaging findings are consistent with postmortem studies and indicate that subcortical gray matter structures should be included in future biomarker studies of ALS. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
155
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 38 publications
14
155
2
Order By: Relevance
“…Several prior neuroimaging studies have suggested that the regions observed in the current neuroimaging study are selectively reduced in C9orf72 expansion relative to sporadic forms of disease, [9][10][11][12][13][14]28 including hippocampus, 10 frontal cortex, 12,13,28 and thalamus, 13,14,29 among other cortical and subcortical regions. One study evaluated longitudinal neuroimaging in a small cohort (n 5 6) of patients with C9orf72 expansion and observed that bilateral thalamus and left globus pallidus decline significantly more than controls, while hippocampus decline did not differ from controls.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Several prior neuroimaging studies have suggested that the regions observed in the current neuroimaging study are selectively reduced in C9orf72 expansion relative to sporadic forms of disease, [9][10][11][12][13][14]28 including hippocampus, 10 frontal cortex, 12,13,28 and thalamus, 13,14,29 among other cortical and subcortical regions. One study evaluated longitudinal neuroimaging in a small cohort (n 5 6) of patients with C9orf72 expansion and observed that bilateral thalamus and left globus pallidus decline significantly more than controls, while hippocampus decline did not differ from controls.…”
mentioning
confidence: 54%
“…Neuroimaging comparisons of C9orf72 expansion relative to C9orf72-negative patients provide preliminary evidence for regional selectivity of gray matter (GM) disease associated with C9orf72 expansion. [9][10][11][12][13][14] In vivo demonstration of effects related to C9orf72 hypermethylation would provide an important method for monitoring response during a disease-modifying treatment trial.…”
mentioning
confidence: 99%
“…To detect subtle regional volume changes of DGM, we performed a shape analysis of DGM (thalamus, putamen, caudate nucleus, nucleus accumbens, and hippocampus), previously reported to be altered in ALS (Agosta et al, 2009;Bede et al, 2013;Chang et al, 2005;Thivard et al, 2007). The shape of the above-mentioned DGM (except the hippocampus, the subfields of which were studied) was analyzed using the FSLs FIRST module version 5.0.0 (Patenaude et al, 2011).…”
Section: Data Processingmentioning
confidence: 99%
“…In addition, studies using positron emission tomographyecomputed tomography (PET-CT), single-photon emission computed tomography (SPECT), magnetic resonance spectroscopy, and diffusion tensor imaging have also shown involvement of deep gray matter (DGM; thalamus, caudatus, putamen, pallidum, hippocampus, amygdala, accumbens), but morphometric changes have been reported sporadically (Sach et al, 2004;Turner et al, 2004;Verstraete et al, 2014). Currently, there is only 1 cross-sectional study that has reported a more detailed morphometric analysis of the DGM in ALS (Bede et al, 2013). This cross-sectional study in 39 ALS patients showed reduced volumes of the left caudate, left hippocampus, and right accumbens in ALS, underscoring the relevance of the subcortical structures in the disease process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation